Novel Polymeric Biochips for Enhanced Detection of Infectious Diseases - Hosseini, Samira; Ibrahim, Fatimah; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book focuses on the creation and development of polymeric platforms (different compositions) from a specific polymer system. This system can be used as an adaptive technique for producing sensitive analytical devices, or for simple integration into existing bioanalytical tools in order to enhance the detection signal.
Current optical biosensors in clinical practice -- Alternative chemical approach -- Biochips Fabrication and surface characterization -- Application of the biochips in dengue virus detection -- Summary -- Appendix.
Keywords: Biomedical engineering; Polymers; Diseases; Biotechnology; Bioinformatics; Biomedical Engineering and Bioengineering; Polymers; Diseases; Biotechnology; Computational and Systems Biology